Scent dogs identify SARS-CoV-2-infections in respiratory samples from experimentally infected ferrets and hamsters—a pilot study - Schulz, Claudia; Twele, Friederike; Meller, Sebastian; ten Hagen, Nele A.; Pilchová, Veronika; Wirz, Katrin; Clever, Sabrina; Meyer zu Natrup, Christian; Volz, Asisa; von Köckritz-Blickwede, Maren; Volk, Holger A. (Frontiers in Medicine, 2024)
Rapid and sensitive diagnostic measures are a pre-requisite for the control of SARS-CoV-2 outbreaks. Dogs detect SARS-CoV-2-infected human individuals with high speed due to their extraordinary olfactory acuity. In the post-pandemic phase of SARS-CoV-2 it is difficult to obtain samples from infected humans for scent dog training. Established animal models for COVID-19 include hamsters and ferrets, which could overcome this shortcoming and have the advantage that samples are generated under controlled conditions. Respiratory samples from humans, hamsters and ferrets infected with SARS-CoV-2 and from ferrets infected with an H7-Influenza A virus were inactivated with β-propiolactone and presented via a device called “Detection Dog Training System” (DDTS). DDTS allows a fast, blinded, randomized, and automated sample presentation without trainer interference. Scent dogs generally showed a similar diagnostic sensitivity (DSe) and specificity (Dsp) for four tested scenarios (S1-4) and as reported previously for respiratory samples from humans. (S1) Human with COVID-19: DSe 88.1 [74.0–100.0% CI95%] and DSp 89.6 [80.6–98.5% CI95%]. (S2) Hamster with COVID-19: DSe 82.4 [74.1–90.7% CI95%] and DSp 96.7 [93.7–99.7% CI95%]. (S3) Ferret with COVID-19: DSe 86.2 [69.8–100.0% CI95%] and DSp 95.1 [89.5–100.0% CI95%]. (S4) Ferrets infected with an H7 Influenza A-virus (IAV) as a distractor: DSe 96.9 [57.2–100.0% CI95%] and DSp 89.86 [40.3–100.0% CI95%]. We provide evidence that scent dogs detect samples from SARS-CoV-2-infected hamsters and ferrets with a similar accuracy as reported for humans. The study highlights that volatile organic compound odor patterns are similar in humans, hamsters, and ferrets after SARS-CoV-2 infection, but distinct after IAV-infection.